2010
DOI: 10.1093/sleep/33.2.225
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Week, Randomized, Double-Blind, Placebo-Controlled Study Evaluating the Effect of Eszopiclone 2 mg on Sleep/Wake Function in Older Adults with Primary and Comorbid Insomnia

Abstract: A Long-Term Safety and Efficacy Study of Eszopiclone in Elderly Subjects With Primary Chronic Insomnia; Registration #NCT00386334; URL - http://www.clinicaltrials.gov/ct2/show/NCT00386334?term=eszopiclone&rank=24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 28 publications
4
82
0
2
Order By: Relevance
“…15 Costs and cost-savings linked to medication are complicated by the inconsistent duration of medication use in clinical trials, even more so in the real world. A brief review of the literature found duration of clinical trials of sedative hypnotics range from short (2 weeks 16,17 ) to moderate (1-3 months [18][19][20] ) to long (6 months 15 ).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…15 Costs and cost-savings linked to medication are complicated by the inconsistent duration of medication use in clinical trials, even more so in the real world. A brief review of the literature found duration of clinical trials of sedative hypnotics range from short (2 weeks 16,17 ) to moderate (1-3 months [18][19][20] ) to long (6 months 15 ).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…One trial attempted to measure the proportion of participants who achieved clinically significant improvement in sleep. 78 It defined clinically significant improvement as the attainment of sleep efficacy equal to or greater than the mean in a group of patients without insomnia. More CBT-I participants achieved clinical improvement than passive controls Sleep onset latency was reported in three trials.…”
Section: Sleep Outcomesmentioning
confidence: 99%
“…39 Participants were randomized to 12 continuous weeks of eszopiclone 2 mg or placebo followed by a 2-week single blind placebo run-out period. Compared to placebo, the authors demonstrated significant improvements in subjective measures of total sleep time, sleep latency and wake after sleep onset in those receiving eszopiclone.…”
Section: Safety and Efficacy Of Eszopiclone In The Elderlymentioning
confidence: 99%
“…No evidence of rebound insomnia was noted following discontinuation of therapy. 39 Of note the three trials detailed are the only studies to date which have examined the use of eszopiclone for the treatment of insomnia in the elderly. All three were industry sponsored.…”
Section: Safety and Efficacy Of Eszopiclone In The Elderlymentioning
confidence: 99%